Clinical safety of 1500 mg oral naltrexone overdose. (7th September 2010) - Reece, Albert Stuart
Abstract : This case represents a clinical overdose of the largest known dose of oral naltrexone, equivalent to the taking of a whole bottle of the oral naltrexone preparation. The patient's intention was to control craving for alcohol and opiates. The patient quickly settled with expectant management. As such it demonstrates that earlier concerns that have been voiced in this area, particularly relating to naltrexone-related hepatotoxicity and depression, may have been overstated, at least in the experience of this patient. This patient's course was marked only by gastric irritation, of which she had some history. As such the present profile provides case report evidence consistent with more robust views of the patient safety of naltrexone itself, and opposing more cautious views. Her polydrug craving was suppressed for a period of 2 weeks, which raises the important question of the mechanism of action of naltrexone's generalised suppression of refractory hedonic consumptive addictive behaviours.